Development of patient information leaflets for fixed, removable, and functional appliances for Arabic-speaking orthodontic patients - Yassir A. Yassir; Ammar S. Kadhum; Hayder F. Saloom; Grant T. McIntyre; David R. Bearn (Saudi Dental Journal)
Objective: To develop Orthodontic Patient Information Leaflets (PILs) in Arabic. Material & method: This study included five phases starting with Arabic translation of existing British Orthodontic Society leaflets; initial face validation with three orthodontists; content validation with ten orthodontists; final face validation with ten orthodontists, five postgraduate students, and ten patients; and re-translation to English prior to comparing the new documents with the original PILs to verify that all the necessary information were included. The content validity index (CVI) assessed item level (I-CVI) and scale level (S-CVI). Results: The three Arabic PILs were face validated with inclusion of mini-screws, rapid maxillary expansion, and interproximal reduction. Content validity was perfect with no item I-CVI < 0.80. The S-CVI/Ave for PIL Fixed Appliances = 0.98, PIL Removable Appliances = 0.98 and PIL Functional Appliances = 0.97. In the final face validation, the three leaflets received 100% agreement from all observers for consistency of leaflet format and style, clarity, readability and use of adequate phrases. Finally, the leaflets were re-translated and the information was checked by native English speakers to ensure the completeness of information. There were no discrepancies and face validity was excellent. Conclusion: Valid PILs for Arabic-speaking patients undergoing orthodontic treatment with fixed, removable, and functional appliances have been developed.